2022
DOI: 10.1093/plcell/koac091
|View full text |Cite
|
Sign up to set email alerts
|

Functional nuclear retention of pre-mRNA involving Cajal bodies during meiotic prophase in European larch (Larix decidua)

Abstract: Gene regulation ensures that the appropriate genes are expressed at the proper time. Nuclear retention of incompletely spliced or mature mRNAs is emerging as a novel, previously underappreciated layer of post-transcriptional regulation. Studies on this phenomenon indicated that it exerts a significant influence on the regulation of gene expression by regulating export and translation delay, which allows the synthesis of specific proteins in response to a stimulus or at strictly controlled time points, e.g. dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In addition to nucleoporins, it was reported that the RNA helicase UAP56 can interacts with ALY and UIEF1/2 (UAP56-INTERACTING EXPORT FACTOR1 and 2), and participate in the regulation of mRNAs nucleocytosolic transport (Pfaff et al, 2018;Ehrnsberger et al, 2019b). Interestingly, a recent study reported that post-transcriptional splicing of mRNAs was involved in their nucleocytosolic exporting (Rudzka et al 2022). Without a doubt, more efforts are needed to study the effects of pre-mRNA splicing on its nuclear exportation in the future research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nucleoporins, it was reported that the RNA helicase UAP56 can interacts with ALY and UIEF1/2 (UAP56-INTERACTING EXPORT FACTOR1 and 2), and participate in the regulation of mRNAs nucleocytosolic transport (Pfaff et al, 2018;Ehrnsberger et al, 2019b). Interestingly, a recent study reported that post-transcriptional splicing of mRNAs was involved in their nucleocytosolic exporting (Rudzka et al 2022). Without a doubt, more efforts are needed to study the effects of pre-mRNA splicing on its nuclear exportation in the future research.…”
Section: Discussionmentioning
confidence: 99%
“…Only non-fully spliced Sm protein transcripts were stored in the CBs. Retained introns are spliced at precisely defined times, and fully mature mRNAs are released into the cytoplasm, where Sm proteins are produced [ 49 ]. Our results show a slightly different pattern retention of RNA with introns in the nuclei of somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in animal cells, mRNA with introns are in nuclear speckles where the post-transcriptional process of their removal may take place [ 60 , 61 ]. In plants, non-fully spliced transcripts were detected in nuclear speckles [ 57 ] in microspores of Marsilea vestita and in CBs in Larix decidua [ 49 ]. Our results showed that RNA with introns accumulated in the nuclei devoid of CBs in leaf cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations